Pengaruh Kualitas Pelayanan Islami, Atribut Produk dan Religiusitas terhadap Kepuasan dan Loyalitas Nasabah Pada Bank Syariah Indonesia Cabang Kudus - Sutono, Sutono; Wismar'ein, Dian; Fitri, Nadila (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
The purpose of this study was to determine whether islamic service quality, product attributes and religiosity influence customer satisfaction and loyalty. The objects of this research are customers of Bank Syariah Indonesia Kudus Branch. This research was carried out by distributing questionnaires to 174 respondents using a purposive sampling technique, namely the researcher determined certain criteria to select consumers who would become respondents. The data analysis method uses SEM- AMOS v.24. Based on the results of this research, it shows that Islamic Service Quality has a positive and significant effect on customer satisfaction. Product attributes have a positive and significant effect on customer satisfaction. Religiosity has a negative and insignificant effect on customer satisfaction. Service quality has a positive and significant effect on customer loyalty. Product attributes have a positive and significant effect on customer loyalty. Religiosity has a negative and insignificant effect on customer loyalty. Satisfaction has a positive and significant effect on customer loyalty